Purine metabolic adaptation protects the endothelium from disturbed flow–induced DNA damage and atherosclerosis - Qian Ma; Yongfeng Cai; Zhidan Zhang; Dingwei Zhao; Yuan Zhao; Peishan Xu; Tammy Lu; Wendy Zhang; Qiuhua Yang; Yaqi Zhou; Varadarajan Sudhahar; Tohru Fukai; et al. (Proceedings of the National Academy of Sciences, 2026)
Despite effective lipid-lowering therapies, atherosclerosis continues to be a leading cause of death, with considerable residual cardiovascular risk. Atherosclerotic lesions develop preferentially at arterial regions exposed to disturbed flow (d-flow), which induces genomic stress, endothelial injury, and barrier dysfunction. Hemodynamic forces are known to reprogram endothelial metabolism, but the role of de novo purine synthesis (DNPS), which supplies nucleotides for genome maintenance and whose terminal steps are catalyzed by the bifunctional enzyme ATIC, remains undefined in atherosclerosis. By integrating bulk and single-cell multiomics with in vitro flow systems and in vivo models, we show that d-flow upregulates DNPS and ATIC genes in vitro and in vivo, in concert with a DNA damage/repair state. Endothelial-specific Atic deletion exacerbates DNA damage, apoptosis, barrier dysfunction, and accelerates atherogenesis, while purine-base supplementation rescues repair defects. We further identify MYC as a mechanosensitive driver of ATIC induction. These findings establish a d-flow-MYC-ATIC-DNPS axis that sustains nucleotide sufficiency for DNA repair and maintains endothelial barrier integrity, suggesting potential endothelial-targeted therapeutic strategies for atherosclerosis.